Reflecting the Faithful economic representation of accounting practices on the quality of accounting information - عبد الحليم, صفوان قصي; صخر, نجاة حميد (Journal of Economics and Administrative Sciences, 2019)
Where the accounting system in Iraq is still using many of these accounting practices according to the legal requirements to measure assets and liabilities away from the measurement that results in information representing the economic essence and represent honestly the financial situation and financial performance and future cash flows, and the needs of users of financial reports to useful accounting information adopted The International Accounting Standards Board (IASB) represents the true representation of accounting information in accordance with the concept of economic substance, which is the basis for the preparation and development of international accounting standards, and because accounting is part of the social sciences that assume The reality is part of the social construction, so it should be understood that the current accounting practices depend on the economic substance of transactions and events and not just the legal form, it is more appropriate to understand the economic reality of the phenomenon to reach its essence and its true meaning and then access to the accounting reality in terms of adopting standards International accounting, which contributes to the enhancement of the quality of accounting information by increasing the degree of appropriateness and honest representation of information and then to the quality of financial reporting and this order will reflect the decisions of users of financial reports, the concept of economic substance In order to provide useful information to the users of financial reports in accordance with the financial reporting objective, the International Standards Board is very important in adopting true representation, so work is being done all over the world to move towards one set of high quality standards through accreditation On international financial reporting standards.